Determinants and Prevalence of Hepatitis B Among Multigravidae Pregnant Women in Bengkulu Province, Indonesia - Diniarti, Fiya; Mohamed Said, Mohamed Saifulaman; Poddar, Sandeep; Ware, Jonathan Andrew; Abd Rashid, Norhashima (YCAB Publisher, 2025)
Background: Morbidity and mortality caused by Hepatitis B Virus (HBV) infection continue to pose a serious global public health concern. Globally, an estimated three million new cases of chronic HBV infection are reported annually, contributing to approximately 51,000 deaths. In Indonesia, HBV is recognized as the fourth leading cause of mortality. Objectives: This study aimed to investigate the factors associated with HBV infection among multigravida pregnant women in Kota Bengkulu, Indonesia, based on an evidence-based approach. Methods: A quantitative case-control study was conducted involving 148 pregnant women, comprising 74 women who tested positive for hepatitis B and 74 who tested negative. The study employed total sampling as the sampling technique. Data were analyzed using chi-square tests and multiple logistic regression to identify significant associations. Results: The analysis revealed significant associations between HBV infection and several variables: age (p = 0.004; OR = 2.867), educational level (p = 0.004; OR = 2.889), type of previous delivery (p = 0.003; OR = 3,753.9), history of blood transfusion (p = 0.002; OR = 2.887), and low level of knowledge (p = 0.004; OR = 2.935). Among these, the most dominant factor associated with HBV infection was a history of blood transfusion (p = 0.002; OR = 3.767). The overall prevalence of hepatitis B in the study population was 0.40%. Conclusion: This study concludes that a history of blood transfusion is the most significant factor associated with HBV infection among multigravida pregnant women in Bengkulu Province, Indonesia. These findings highlight the need for enhanced screening and preventive measures, particularly in maternal healthcare settings. Keywords: Hepatitis B; multigravida pregnant women; education level; delivery history; blood transfusion history